The diversity and traditional knowledge of wild edible fruits in Bengkulu, Indonesia - Suwardi, Adi Bejo; Syamsuardi; Erizal Mukhtar; Nurainas (Ethnobotany Research and Applications, 2023)
Background: Wild edible fruit plant species (WEFs) contribute significantly to human well-being. These plants have a high nutritional value and are a source of novel alleles/genes that are important in developing new and improved crop cultivars to promote sustainable food security. However, most WEFs are less well-known and underutilized. This study aimed to investigate wild edible fruit species diversity and their potential in the Bengkulu region, Indonesia. Methods: The ethnobotanical study was carried out in eight villages from four districts of Bengkulu province, Indonesia, i.e. Mukomuko, Lebong, Rejang Lebong, and Bengkulu Selatan. The ethnobotanical survey was carried out from July to September 2022 and included 383 randomly selected respondents. The ethnobotanical investigation uses semi-structured questionnaires to gather information on the traditional knowledge of WEFs. Plant specimens were collected and identified in herbarium ANDA, Universitas Andalas. Results: A total of 73 wild edible fruit plant species belonging to 37 genera and 26 families were recorded in the study area. Most of the plant species were trees (87.7%), followed by shrubs (5.5%), climbers (4.1%), and herbs (2.7%). Forty-eight (79.5%) species were discovered in the forest, 7 (9.6%) in the farmlands, and 8 (11%) in both the forest and the farmlands. WEFs are mostly consumed as food. Artocarpus integer, Mangifera odorata, Pometia pinnata, Flacourtia rukam, Durio oxleyanus, Baccaurea racemosa, Bellucia pentamera, Baccaurea macrocarpa, Baccaurea polyneura, and Mangifera foetida. Artocarpus integer are the most preferred WEFs by their taste quality. Besides foods, WEFs have multi purposes including as traditional medicine, construction, agricultural tools, fuelwood, and fodder. Indigenous knowledge of WEFs was significantly associated with districts, age groups, and educational levels. Conclusion: Bengkulu has a diverse range of WEFs, but only a small proportion has been used by local people, particularly as food. Promotion and domestication of WEFs should be a primary concern in Bengkulu in order to take advantage of their nutritional value and potential economic value. Moreover, integrating knowledge related to WEFs into the educational curriculum is critical for educating the next generation regarding the potential of WEFs in the future. Keywords: Bengkulu, biodiversity, local knowledge, wild fruits, underutilized plants